Prehistoric Quarries and Terranes : The Modena and Tempiute Obsidian Sources - Shott, Michael J. (Michael Joseph) (Book collections on Project MUSE., 2021)
"This project is Shott's report on the extensive analysis of a large sample of flake debris and products from the Modena and Tempiute obsidian quarries in eastern Nevada. Archaeologists dealing with the mass of quarry material will find useful information about analyses of reduction, flake assemblages and preform data that should be transferrable to other quarry sites globally. Shott sought to "1) devise and implement efficient but rigorous (i.e. probabilistic) sample designs for spatially extensive, abundant quarry deposits; and 2) to test a behavioral-ecology model of the staging of resource use, the field-processing model (FPM)." However, data collection and initial analysis also required additional analyses be undertaken to appropriately address research questions. As a result, this manuscript details a "diverse and comprehensive set of methods to a large, systematically acquired dataset." It supports the conclusion that the Modena quarry was used by small groups though time"--